New educational strategies in contemporary digital environment. (2016) - Smyrnova-Trybulska, Eugenia; Noskova, Tatiana; Pavlova, Tatiana; Yakovleva, Olga; Morze, Nataliia
This paper prepared by an international team of authors, focuses on the following conceptual aspects: new educational strategies in the contemporary digital environment on the basis of a study in the framework of the international project IRNet-International Research Network. In particular, the paper describes some of the results of a survey for students and academic teachers conducted within the framework of the project. During the study common and specific categories of university informational educational strategies were examined as well as a teachers' personal attitude to different educational strategies were tested. The paper contains data, describing the situation at universities in Poland, Russia and Ukraine.